Pemberian Aromaterapi Bunga Mawar terhadap Penurunan Tekanan Darah pada Wanita Lanjut Usia di UPTD Panti Sosial Lanjut Usia Tresna Werdha Natar Lampung Selatan - Ana Mariza; Annisa Umi Kalsum (Jurnal Kesehatan, 2017)
Hypertension is one of the world's number one cause of death. Cases of hypertension were increased approximately 80%, especially in developing countries. The incidence of hypertension in Lampung has 77.521 people in 2014.  Then, hypertension  was  the  most  prevalent diseases in  Social  Institutions  Elderly, Tresna  Werdha, Natar, South  Lampung, as many as 32 people (60.37%). Treatment of hypertension could be done with aroma therapy. One of the plants that have function as aroma therapy were roses. The purpose of this study was known the effect of roses aroma therapy to reduction of blood pressure in elderly women in Social Institutions Elderly, Tresna Werdha, Natar, South Lampung, in 2016. This study was a quantitative research, with quasi experimental design, one group pretest-posttest design. Population in this study were all elderly women in Social Institutions Elderly, Tresna Werdha, Natar, South Lampung. Sample total were 32 people. Hypothesis was tested with paired samples t-test. Results of univariate analysis showed that average blood pressure, before and after giving treatment with roses aroma therapy were 121.04 and 113.02, respectively. Results of bivariate analysis showed that roses aroma therapy affected to reduction of blood pressure in elderly women in Social Institutions Elderly, Tresna Werdha, Natar, South Lampung, in 2016 (p-value=0.000).